Learning Media Simulators Lighting System with Proteus Software in Vocational Schools - Imamhady, Hilmy Wikan; Handoyono, Nurcholish Arifin (Universitas Pendidikan Ganesha, 2024)
Simulators are a medium that students need to be able to learn safely, efficiently, and effectively. Simulators can be used as an alternative pre-practice media that can support the smooth learning process of students to avoid trial and error incidents. Therefore, this research aims to develop and test the feasibility of a lighting system simulator for automotive electrical subjects. This research is a Research and Development (R&D) study of Borg and Gall, the steps of this development research consist of 10 steps, namely (1) Identifying potential problems, (2) Gathering information, (3) Design, (4) Design validation, (5) Design improvement, (6) Product trial, (7) Product revision, (8) Usage trial, (9) Final product revision, and (10) Mass production. The data collection method involved two material experts and one media expert. The product usage trial was conducted on students in the automotive class at Vocational High School. The data collection technique in this study used a questionnaire, and the data analysis used was descriptive quantitative. The research results are that the lighting system simulator that has been developed is very suitable for use in learning, so it can be used to make it easier for students in the lighting system learning process. Students can use the simulator for independent or group learning.